Cows In Action First Cow on The Mooon - "Cole, Steve" (Red Fox: London, 2011)
The time-travelling cows are going into space! When evil ter-moo-nators appear on the farm with a plan to invade the Earth it seems like business as usual for McMoo, Pat and Bo. But when the same two villains arrive u as younger versions of themselves, the gang realize this is an en-cow-nter of the strangest kind
Keywords: Cattle Fiction